PERANCANGAN MONITORING JARAK JAUH KETINGGIAN AIR PADA BENDUNGAN MENGGUNAKAN SISTEM ANDROID VIA JARINGAN WI-FI - irma sika girsang (Saintia Fisika, 2013)
In this writing of this essay has discussed a problem about “DESIGN OF DISTANCEMONITORING IN DAM LEVEL USING ANDROID SYSTEM VIA WI-FI NETWORK”. Thistools used for remote monitoring from distance ofthe water level atthe dam using android. Soit can easer us to monitor the dam though from a great distance. Simulation of this dam usingAT89S51 Microcontroller, conductivity sensor, PSA, Relay, water pump system also Androidand PC as Server and Receiver when the tool works. conductivity sensor works read the leverof water and then sent to e server that can be monitored from great distance using android.This tools work when sensor detect the level of water then the microcontroller and sent thedata to the PC by RS232 and in the computer displayed visualization the lever of water andbroadcasted by wifi network.This program created to readthe level of water and detected bysensor. The data sent to the PC by serial port.Keywords: Conductifity Sensor, AT89S51, Android system, VNC